Boyd the fighter pilot who changed the art of war - Coram, Robert (Back Bay Books/Little, Brown, 2002)
A detailed portrait of American fighter pilot John Boyd examines his distinguished military career during the Korean War and his postwar efforts as a military theorist who took on the entrenched Pentagon bureaucracy to transform the art of modern warfare and the American military with his revolution